Self-Decoupled 8-Element Dual Polarized MIMO Antenna for B5G Handsets With Sub-6 GHz and mmWave Integration - Ali Sufyan; Syed Ahson Ali Shah; Khan Bahadar Khan; Izaz Ali Shah; Arif Ullah; Tauseef Ahmad Siddiqui; Saiful Islam; Hyoungsuk Yoo (IEEE Access, 2024)
This study examines a single-fed, self-isolated, dual-band, 8-element multiple-input multiple-output (MIMO) antenna system for fifth-generation (5G) and beyond-5G (B5G) handsets. The proposed antenna is designed by an innovative composition of two F-shaped slots backed by a slotted ground plane, enabling a dual-band operation in the sub-6 GHz (4.7 to 4.9 GHz, n79) and millimeter wave (mmWave) (28 to 29 GHz, n257) frequency bands. High isolation of >14.4 dB and >25 dB and a high diversity gain of >9.9 dB were achieved at the respective frequency bands without using additional decoupling techniques, exhibiting an efficiency of approximately 90% with high gains of 4.9 and 7.2 dBi at the n79 and n257 bands, respectively. The antenna demonstrates excellent MIMO performance regarding very low envelope correlation coefficient (<0.001), total active reflection coefficients (<10 dB and −24 dB), and mean effective gain ( $\lt -7.3$ dB and −7 dB). In addition to the safety evaluations, the performance is verified in a realistic mobile device to ensure practical feasibility. The evaluations showed promising results, demonstrating that the proposed design is a suitable, compact, and highly effective MIMO solution for 5G and B5G handsets.